Quantitative estimation of plum pox virus targets acquired and transmitted by a single Myzus persicae - Moreno, Aránzazu; Fereres, Alberto; Cambra, Mariano (2017)
The viral charge acquired and inoculated by single aphids in a non-circulative transmission is estimated using plum pox virus (PPV). A combination of electrical penetration graph and TaqMan real-time RT-PCR techniques was used to establish the average number of PPV RNA targets inoculated by an aphid in a single probe (26,750), approximately half of the acquired ones. This number of PPV targets is responsible for a systemic infection of 20% on the inoculated receptor plants. No significant differences were found between the number of PPV RNA targets acquired after one and after five intracellular punctures (pd), but the frequency of infected receptor plants was higher after 5 pd. The percentage of PPV-positive leaf discs after just 1 pd of inoculation probe (28%/4,603 targets) was lower than after 5 pd (45.8%/135 x 10(6) targets). The methodology employed could be easily extended to other virus-vector-host combinations to improve the accuracy of models used in virus epidemiology.